FAKTOR-FAKTOR YANG MEMPENGARUHI KORPORASI DI INDONESIA MELAKUKAN MANAJEMEN INTERNET CRISIS POTENTIAL - Tri Istining Wardani; Dwi Sudjanarti (Politeknik Negeri Malang, 2019)
This study tries to analyze the factors in the Internet Crisis Potential (ICP) model of ICP management in companies in Indonesia. The research suggestions used are survey research methods, through primary data collection obtained directly from original sources through oral and written questions. While this type of research is explanatory research / explanatory research that explains the causal relationship / causes between the research variables with hypothesis testing. The object of this research is companies in Indonesia that implement crisis management through the Internet. The population in this study are all companies from the Information Technology Department and corporate communication departments from various business sectors in Indonesia. Samples were taken using purposive sampling technique. The result of the equation Y = 4.930 - 0.030X1 + 0.106X2 - 0.337X3 + 0.360X4. The result of the Adjusted R Square determination coefficient test is 0.219%, and that partially the views and experiences regarding the preparation of